Efecto de dos Niveles de proteína en Dietas alimenticias para la Producción de Gamitana (Colossoma macropomum), Boquichico (Prochilodus nigricans) y Tilapia (Tilapia sp) criados en policultivo - Rengifo García, Fernando (1999)
During a period of 120 days , from February to June 98 , it was studied the efect of two levels of protein , in the diet (15% and 25%) for gamitana production (Colossoma macropomum), boquichico (Prochílodus nigricans) and Tilapia (IiJapia sp) rised in polibrood with tho treatments and one witness in arder lo stablish the ríght protein for the production with fish flour as a base with soy-bean font, ground com, font rice and mineral salt l % (supamin difos) in San Martín Región. The result showed differences in the tho treatrnents with a bíologica replay and not meant i n the treatments in the way of production in polybreedíng with tbe materials mentioned. However it was reported a better biological answer in the samples with a level of 25% of net protein in the diet, with an increasing of weight daily of 1.63 grams for Tilapia sp, 3.4 grams for Colossoma macropomum and 1.21 grams Cor Prochilodus nigricans with a production of 8,505 Kg/Ha with a density of 1.5 fish m1 in amounts of 1.0 , 0.35 and 0. 15 respectíble, been the protein better of 15% of protein net with 40.7 and Colossoma macrooomum after of Tilapia sp , tbe samples more efficent for bussiness.